Molecular evidence for the presence of malaria vector species a of the Anopheles annularis complex in Sri Lanka - Surendran, S.N.; Gajapathy, K.; Kumaran, V.; Tharmatha, T.; Jude, P.J.; Ramasamy, R. (BioMed Central Ltd, 2011)
Background: Anopheles annularis s.l. is a wide spread malaria vector in South and Southeast Asia, including Sri Lanka. The taxon An. annularis is a complex of two sibling species viz. A and B, that are differentiated by chromosome banding patterns and ribosomal gene sequences in India. Only species A is reported to be a malaria vector in India while the occurrence of sibling species in Sri Lanka has not been documented previously. Findings. Anopheline larvae were collected at a site in the Jaffna district, which lies within the dry zone of Sri Lanka, and reared in the laboratory. Emerged adults were identified using standard keys. DNA sequences of the D3 domain of 28S ribosomal DNA (rDNA) and the internal transcribed spacer-2 (ITS-2) of the morphologically identified An. annularis were determined. BLASTn searches against corresponding An. annularis sequences in GenBank and construction of phylogenetic trees from D3 and ITS-2 rDNA sequences showed that the Sri Lankan specimens, and An. annularis s.l. specimens from several Southeast Asian countries were closely related to species A of the Indian An. annularis complex. Conclusions: The results show the presence of the malaria vector An. annularis species A in Sri Lanka and Southeast Asia. Because An. annularis vectors have been long associated with malaria transmission in irrigated agricultural areas in the Sri Lankan dry zone, continued monitoring of An. annularis populations, and their sibling species status, in these areas need to be integral to malaria control and eradication efforts in the island.
Keywords: Anopheles annularis; malaria vector; ribosomal genes; sibling species; Southeast Asia; Sri Lanka